PELATIHAN PENYUSUNAN LESSON DESIGN BERBASIS LESSON STUDY - Muhdar, Syafruddin; Fujiaturrahman, Sukron; Bilal, Arpan Islami; Winata, Aliahardi; Muttaqien, Zedi; Waluyan, Roby Mandalika; Sirajuddin, Sirajuddin (JCES (Journal of Character Education Society), 2023)
Abstrak: Pembelajaran abad 21 diharapkan dapat membekali peserta didik dengan kemampuan 4Cs, yakni kemampuan: 1) berkomunikasi (communication), 2) berkolaborasi (collaboration), 3) berpikir kritis dan pemecahan masalah (critical thinking and problem solving), dan 4) kreativitas dan inovasi (creativity and innovation). Metode pelatihan melalui 3 tahapan. 1 Tahap perencanaan, 2. Tahap Pelaksanaan dan 3. Tahap Evaluasi. Pelatihan penyusunan Lesson Desain dilaksanakan melalui 3 tahapan. Tahap pertama perencanaan dilalui dengan koordinasi dengan observasi. Tahap kedua dilakukan dengan pemberian materi dan penyususnan lesson desain secara berkelompok. Tahap ketiga evaluasi dengan melakukan penilaian terhadap lesson desain yang dibuat. Jumlah peserta yang terlibat dalam pelatihan ini yaitu 5 orang. Hasil dari pelatihan menunjukkan peserta terlihat antusias dan tertarik membuat lesson desain. Ini terlihat dari hasil yang dibuat peserta sudah sesuai dengan format yang ditentukan.Abstract: 21st century learning is expected to equip students with 4Cs abilities, namely the ability to: 1) communicate, 2) collaborate (collaboration), 3) critical thinking and problem solving (critical thinking and problem solving), and 4) creativity and innovation (creativity and innovation). The training method goes through 3 stages. 1 Planning stage, 2. Implementation Phase and 3. Evaluation Stage. Training on the preparation of Design Lessons is carried out through 3 stages. The first stage of planning is passed in coordination with observation. The second stage is carried out by providing material and compiling design lessons in groups. The third stage of evaluation is by assessing the design lessons made. The number of participants involved in this training is 5 people. The results of the training showed that participants looked enthusiastic and interested in making design lessons. This can be seen from the results made by participants in accordance with the specified format.